Radiation pattern control of microstrip antenna in elevation and azimuth planes using EBG and pin diode. - M. K Abdulhameed; M. S. Mohamad Isa; Z. Zakaria; I.M. Ibrahim; Mowafak K. Mohsen (Institute of Advanced Engineering and Science, 2019)
An important issue in wireless communication systems, which is related to the antenna gain degradation in case of changing the main direction of the antenna radiation pattern, this variation is not approval in many communications systems. In order to improve antenna radiation performances, Electromagnetic band gap (EBG) - antenna with radiation pattern control capability is presented. Mushroom-like EBG structure for suppressing surface waves has been combined, with the switching diode to produce the radiation pattern control with improving antenna characteristics of gain, directivity and efficiency. EBG of several cells are surrounded the patch antenna and placed symmetrically for the two opposite sides, generating different radiation patterns control ability in both the elevation (E) (-20° < φ < 20°) and azimuth (Z) planes (−18° < θ < 18°). At the ground plane of antenna the diodes have been switched ON and OFF states, the EBG sector properties in stop band (connecting vias) and pass band (disconnecting vias) are altered. Using CST Microwave Studio (CST MWS) the results show the flexibility in radiation pattern control for the Z and E planes using only four diodes. Antenna directivity of 10 dBi, gain 9.86 dB and efficiency 96.5% at the operating frequency of 6 GHz, more results for all direction has been stated in Table1. Significantly, unlike a conventional beam steering, this method does not suffering from gain degradation and the main lobe gain is approximately constant for all steerig angles.